The Influence of Competence, Training, and Work Environment On The Performance of SD Alam Insan Cemerlang Teachers - Audilla Putri Munggaran; Sri Astuti Pratminingsih (Dinasti Publisher, 2025)
SD Alam Insan Cemerlang is a school based on a combination of natural and Islamic schools that aims to develop the potential of students, shape and strengthen the character of students. from the results of the data obtained, there has been a decrease in the performance of SD Alam Insan Cemerlang teachers for almost the last 2 years as seen from performance management data on the Teaching Media Platform (PMM). factors that affect teacher performance include competence, training, and work environment. This study aims to analyze the effect of teacher competence, training, and work environment on teacher performance at SD Alam Insan Cemerlang. The research method used is quantitative with a descriptive verification approach, the data was collected using a questionnaire distributed to 30 teachers of SD Alam Insan Cemerlang. The sample size was determined using nonprobability sampling technique. The analytical tool used in this research is SPSS Windows 25. The results showed that (1) competence has a positive effect on teacher performance, (2) training has a positive effect on teacher performance, (3) the work environment has a positive effect on teacher performance. This study implies that improving competence through competence, training that is relevant to the needs of teachers, and creating a conducive work environment can improve teacher performance.